Formation and deposition of polymer nanostructures on surfaces - Wieland, Maria B. (2015)
In this thesis different routes to the formation of extended two-dimensional polymers via on-surface coupling reactions are presented. Polyphenylene networks formed by the molecules tri-(bromo-phenyl)-benzene via on-surface Ullmann coupling reactions are investigated with scanning tunnelling microscopy. The polyphenylene networks with near complete surface coverage exhibit a vitreous structure. The network is composed of linked molecules forming polygons with four to eight edges. A different set of covalently bound molecular nanostructures can be formed on a surface upon thermal activation of porphyrin building blocks. Porphyrin molecules are covalently linked to form one dimensional chains or extended networks using either Ullmann-type coupling reactions to link brominated phenyl sidegroups, or Glaser-Hay-type coupling to form butadiene links via reaction of two phenyl-ethylene sidegroups. The resulting polymers are investigated with scanning tunnelling microscopy and Raman spectroscopy. In a complementary strand of research it is shown that thin films of C60 can promote adhesion between a gold thin film deposited on mica and a solution-deposited layer of the elastomer polymethyldisolaxane (PDMS). This molecular adhesion facilitates the removal of the gold film from the mica support by peeling and provides a new approach to template stripping which avoids the use of conventional adhesive layers. The fullerene adhesion layers may also be used to remove organic monolayers and thin films as well as two-dimensional polymers such as the porphyrin networks discussed previously. Following the removal from the mica support the monolayers may be isolated and transferred to a dielectric surface by etching of the gold thin film, mechanical transfer and removal of the fullerene layer by annealing/dissolution. The use of this molecular adhesive layer provides a new route to transfer polymeric films from metal substrates to other surfaces. A different set of experiments investigated porphyrin nanorings and their interaction with C60 on a gold surface. Solvent-induced aggregates of nanoring cyclic polymers may be transferred by electrospray deposition to a surface where they adsorb as three dimensional columnar stacks. The observed stack height varies from single rings to three stacked rings. Those stacked layers of cyclic porphyrin nanorings constitute nanoscale receptacles with variable height and diameter which preferentially adsorb sublimed C60 molecules. Using scanning tunnelling microscopy the filling capacity of these nanoring traps is determined, as is the dependence of adsorbate capture on stack height and diameter.